DEVELOPMENT OF AN ADVERSE DRUG REACTION AVOIDABILITY ASSESSMENT TOOL. Issue 8 (11th July 2014) - Bracken, L; Kirkham, J; Nunn, A; Pirmohamed, M; Turner, M
Abstract : Aim: To develop and test a new adverse drug reaction (ADR) avoidability assessment tool (AAT) that is more suitable for use in paediatrics but which is also generalisable and applicable to a variety of other settings. Methods: The new AAT was based on the Hallas scale1 and the initial draft of the tool was developed via a consensus approach. Phase one consisted of three parts (defining the tool, modifying the tool and refining the tool) involving two multidisciplinary teams (MDT) each comprising a research children's nurse, paediatrician and pharmacist. Phase two involved the independent assessment of 50 ADR cases reports of adverse drug reactions from a paediatric inpatient study by six reviewers acting independently. Results: Phase 1: the assessment of 20 ADR cases by two MDTs showed agreement between the groups on 13/20 cases with a kappa score of 0.29 (95% CI −0.04 to 0.62). Group members commented that a mixture of professions was needed to give a full assessment of avoidability. Phase 2: the individual assessment of 50 ADR case reports by six individual reviewers where pair-wise kappa scores ranged from poor to good (0.12 to 0.75) and percentage exact agreement (%EA) ranged from 52–90%. Stronger agreement was found within professions than between professions. Conclusion: The new AAT showed mixed inter-rater reliability (IRR) in the individual assessment phase; further testing in a group setting is required to develop and validate the tool. The next step in the development process will be to investigate how groups make decisions and the factors that influence decision making.